1984
DOI: 10.1136/jcp.37.9.993
|View full text |Cite
|
Sign up to set email alerts
|

Combined external quality assessment of cytology and histology opinions: a pilot scheme for a cluster of five laboratories.

Abstract: SUMMARY A cluster of five self selected cytodiagnostic laboratories circulated 70 cervical/vaginal smears and 50 sputum smears in a series of five week cycles. Histological sections related to the abnormal smears were also circulated. Proportions of agreement and disagreement were analysed for cervical and sputum smear reports against the original report (and by implication against the consensus); corresponding calculations were made for the histological reports. Cytological and histological correlation was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
13
1

Year Published

1987
1987
2007
2007

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 11 publications
0
13
1
Order By: Relevance
“…In a study with similar characteristics to the present one [25], the weighted ĸ coefficients for the grading of the malignancies detected in urine cytologies were 0.5 and 0.57, respectively, for urine specimens from patients with primary and recurrent tumors. In another study, the concordance between five departments of pathology for the cytological diagnosis of smears of cervical mucus and sputum was excellent (0.78 and 0.82, respectively) [26]. With regard to the performance of the unweighted ĸ statistic, the calculation of the weighted ĸ coefficient better reflects clinical reality: when one evaluates the ordinal scales composed of categories of increasing severity, some discrepancies are more serious than others.…”
Section: Discussionmentioning
confidence: 99%
“…In a study with similar characteristics to the present one [25], the weighted ĸ coefficients for the grading of the malignancies detected in urine cytologies were 0.5 and 0.57, respectively, for urine specimens from patients with primary and recurrent tumors. In another study, the concordance between five departments of pathology for the cytological diagnosis of smears of cervical mucus and sputum was excellent (0.78 and 0.82, respectively) [26]. With regard to the performance of the unweighted ĸ statistic, the calculation of the weighted ĸ coefficient better reflects clinical reality: when one evaluates the ordinal scales composed of categories of increasing severity, some discrepancies are more serious than others.…”
Section: Discussionmentioning
confidence: 99%
“…This interactive mode is attractive, but although fatigue is reduced, it does not overcome the subjectivity of the human examination both in review of the dat tape and in the microscopic examination of selected cells on the slide. This is a well-recognized problem in reporting both histology and cytology, 7,14,17 and there can also be a variation, called "drift," when the same observer rereports material after an interval of a few months. 1,10 Table II illustrates interobserver variation in the present series and also the variability that is possible, depending on the background of the observers.…”
Section: Discussionmentioning
confidence: 99%
“…After all this, however, there is still the human interactive element, which may have the same problems of subjectivity, particularly with low grade squamous intraepithelial lesions (SILs), as are found when cervical smears and cervical biopsies are read manually. 7,14,17 In pursuance of a previous report, 5 we designed a minitrial to investigate the effect of all these factors and the potential variation between different grades of personnel using the system.…”
mentioning
confidence: 99%
“…25 In this study, the ability to discriminate reliably between CIN 2 and CIN 3 was high (mean variability of index B was 0.89). Recently, Husain et al 36 found a crude agreement of 87% and a nonweighted κ of 0.79 in a comparison of the reporting patterns of 5 laboratories using 3 main diagnostic categories (benign, CIN, and malignant). 36 In our approach, using the diagnostic categories of TBS 2001, including ASC and AGC, a crude agreement of 0.67% was obtained among the 4 laboratories, with nonweighted κ of 0.45 (Table VII).…”
Section: Discussionmentioning
confidence: 99%
“…[32][33][34][35][36][37][38][39][40] On one hand, data provided by performance evaluation systems are subject to potential bias. 32,34,36 According to EQA principles, any EQA system for cytology laboratories should assess the performance of each participant individually, as well as that of the laboratory as a whole. 37 Circulated slide sets among the laboratories is the core of the interlaboratory QC and quality improvement (QI), and it is the only method to evaluate interobserver and interlaboratory reproducibility.…”
Section: Discussionmentioning
confidence: 99%